Sulfate-resistant portland cement composite cementitious material based on retired wind power blade cement clinker and preparation method and application thereof
By scientifically compounding cement clinker from decommissioned wind turbine blades with other materials, a composite cementitious material with high C3S and low C3A was prepared. This solved the technical contradiction between the resource utilization of decommissioned wind turbine blades and the high strength and high corrosion resistance of cement, achieving a balance between high early strength and ultimate resistance to sulfate attack, making it suitable for harsh environments such as marine engineering.
Patent Information
- Application Number
- CN202610576833.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-28
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies make it difficult to effectively utilize retired wind turbine blade resources, and traditional sulfate-resistant silicate cement struggles to balance high strength and high corrosion resistance, resulting in slow early strength development and failing to meet the demands of modern high-strength, high-durability concrete engineering.
By scientifically blending cement clinker from retired wind turbine blades with granulated blast furnace slag powder, silica fume, gypsum, and fly ash, and through precise control of mineral composition and grinding, a high-C3S, low-C3A composite cementitious material is prepared. This eliminates the main inducing factor of calcium hydroxide, forms a synergistic cementitious system, and achieves high early strength and ultimate resistance to sulfate attack.
This technology enables the efficient resource utilization of retired wind turbine blades and produces silicate cement composite cementitious materials that combine high early strength with excellent resistance to sulfate attack, making them suitable for high-performance concrete engineering in harsh sulfate attack environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the interdisciplinary field of special cement and solid waste resource utilization, and in particular to a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, its preparation method, and its application. Background Technology
[0002] Currently, marine engineering, salt lakes, and saline-alkali lands, which are environments prone to strong sulfate corrosion, place stringent demands on cement-based cementitious materials for both high strength and high corrosion resistance. The core principle of traditional sulfate-resistant silicate cement is to improve its corrosion resistance by reducing the tricalcium aluminate (C3A) content. However, this method often results in a low content of tricalcium silicate (C3S), which contributes most to the early strength of the clinker, leading to slow early strength development and making it difficult to meet the needs of modern high-strength, high-durability concrete engineering.
[0003] The rapid development of the wind power industry has brought about the challenge of disposing of retired wind turbine blades. Wind turbine blades are mostly made of glass fiber reinforced composite materials, and current disposal methods often use them as concrete aggregate or low-volume mineral admixtures. This not only makes it difficult to completely eliminate their organic components, but also results in low resource utilization and added value. Although retired wind turbine blades contain elements such as silicon and aluminum, theoretically they can be used as substitute raw materials for cement raw materials, how to effectively incorporate them into the raw material system and stably prepare clinker with a specific mineral composition that simultaneously possesses high C3S to ensure early strength and low C3A to improve corrosion resistance remains an unsolved technical challenge. More importantly, even if such high-C3S clinker is obtained, it still has inherent defects in sulfate environments: the hydration of high-C3S clinker produces a large amount of calcium hydroxide, which is the main attack point of sulfate corrosion. It easily reacts with the corrosive medium to form gypsum and expansive ettringite, causing expansion and cracking of the concrete structure, becoming an inherent performance bottleneck for high-strength clinker used in corrosion-resistant environments.
[0004] Existing technologies have limited ways to utilize retired wind turbine blades for high-value resource recovery, and they also cannot effectively resolve the technical contradiction between high strength and high corrosion resistance in cement. Summary of the Invention
[0005] The main objective of this invention is to provide a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, its preparation method, and its application. The technical problem to be solved is how to synergistically achieve the high-value resource utilization of decommissioned wind turbine blades and prepare a silicate cement composite cementitious material with both high early strength and excellent sulfate resistance, such that its 3-day compressive strength is ≥15MPa, its 28-day compressive strength is ≥52MPa, and its 28-day corrosion resistance coefficient K is ≥1.1, thus making it more suitable for practical application.
[0006] The objective of this invention and the technical problem it solves are achieved through the following technical solution. According to this invention, a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades comprises, by mass percentage: 32-40% cement clinker from decommissioned wind turbine blades, 42-50% granulated blast furnace slag powder, 5-9% silica fume, 3-5% gypsum, and 5-8% fly ash; wherein, by mass percentage, the mineral composition of the cement clinker from decommissioned wind turbine blades comprises: C3S 72.0-80.0%, C2S 6.0-14.8%, C3A ≤ 3.6%, C4AF 9.9-10.7%, and the total amount of C3S and C2S ≥ 85%.
[0007] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0008] Preferably, the sulfate-resistant silicate cement composite cementitious material has a specific surface area ≥ 420 m². 2 / kg.
[0009] Preferably, the sulfate-resistant silicate cement composite cementitious material has a 3-day compressive strength ≥15MPa, a 28-day compressive strength ≥52MPa, and a 28-day corrosion resistance coefficient K ≥1.1.
[0010] The objective of this invention and the technical problem it solves are achieved by the following technical solution. A method for preparing a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, according to this invention, includes the following steps: metering and mixing raw materials according to the designed proportions, and grinding the mixture to a specific surface area ≥ 420 m². 2 / kg, to obtain cementitious material; by mass percentage, the raw materials include: 32~40% cement clinker from decommissioned wind turbine blades, 42~50% granulated blast furnace slag powder, 5~9% silica fume, 3~5% gypsum, and 5~8% fly ash; by mass percentage, the mineral composition of the cement clinker from decommissioned wind turbine blades includes: C3S 72.0~80.0%, C2S 6.0~14.8%, C3A≤3.6%, C4AF 9.9~10.7%, and the total amount of C3S and C2S ≥85%.
[0011] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0012] Preferably, in the preparation method, the cement clinker for the decommissioned wind turbine blades is prepared according to the following steps: raw materials for raw meal preparation are measured and mixed according to the designed proportion; the mixture is ground to obtain raw meal; the raw meal is preheated, decomposed, calcined, and cooled to obtain clinker containing decommissioned wind turbine blades; by mass percentage, the raw materials for raw meal preparation include: limestone 81.91-82.87%, clay 0.77-2.34%, bauxite 0.78-1.57%, iron ore 1.50-1.64%, sandstone 6.34-8.22%, and dried decommissioned wind turbine blade powder 5.0-7.0%.
[0013] Preferably, in the preparation method, the decommissioned wind turbine blade powder is obtained by dismantling, removing metal connectors, coarsely crushing, finely crushing and grinding decommissioned wind turbine blades, wherein more than 90% of the particles have a particle size of <80μm.
[0014] Preferably, in the preparation method, the decommissioned wind turbine blade powder contains ≥50% SiO2, ≥17% Al2O3, and ≤15% loss on ignition by mass percentage.
[0015] Preferably, in the preparation method, the residue of the raw material on an 80μm sieve is ≤10%.
[0016] Preferably, in the preparation method, the granulated blast furnace slag powder is of grade S95 or higher.
[0017] The objective of this invention and the technical problem it solves are achieved by the following technical solution. The application of a sulfate-resistant silicate cement composite cementitious material prepared according to the aforementioned method in the field of concrete or building materials technology.
[0018] By employing the above technical solution, the sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades proposed in this invention, its preparation method, and its application, have at least the following advantages: 1. This invention realizes the efficient and high-value resource utilization of retired wind turbine blades. It introduces retired wind turbine blades as key silicon-aluminum raw materials (5.0%~7.0%) into cement raw materials. Their organic components are completely decomposed and utilized during calcination, successfully transforming solid waste into a component of high-performance clinker, and significantly improving resource value.
[0019] 2. This invention overcomes performance bottlenecks through clinker phase composition design and material composite synergistic process design. On one hand, it precisely controls the proportions of each raw material to strictly control their percentage values, thereby stably producing a special clinker with high C3S (72~80%) and low C3A (≤3.6%), ensuring high product strength. Then, using this clinker (32~40%) as the core, it is scientifically compounded and co-ground with a high proportion of granulated blast furnace slag powder (42~50%), silica fume, gypsum, and fly ash to form a synergistic cementitious system. The aforementioned highly active admixtures greatly consume the calcium hydroxide produced during clinker hydration, fundamentally eliminating the main cause of sulfate attack, thus synergistically solving the traditional problem of balancing high early strength and ultimate sulfate resistance. The corrosion resistance mechanism of the cementitious material of this invention lies in the secondary hydration reaction of highly active blast furnace slag, silica fume, and fly ash, which consumes a large amount of calcium hydroxide generated during clinker hydration, reducing alkaline enrichment sites in the slurry. Simultaneously, it optimizes the interface structure, reducing interconnected pores and erosion channels, making it difficult for sulfate ions to penetrate and preventing the formation of expansive products such as gypsum and ettringite. This transforms the cementitious system from passive corrosion resistance to active erosion inhibition, achieving a high corrosion resistance performance with a 28-day corrosion resistance coefficient K≥1.1. The cementitious material system of this invention uses a ternary compound of granulated blast furnace slag powder, silica fume, and fly ash. Silica fume provides early activity and rapidly fills pores; slag powder provides the main pozzolanic activity, consuming calcium hydroxide over a long period; and fly ash optimizes workability and volume stability. The three components synergistically achieve a balance of early strength, high corrosion resistance, and low shrinkage, which cannot be achieved by a single component.
[0020] 3. This invention endows the product with excellent comprehensive performance and wide applicability. The composite cementitious material prepared by this technical solution has both good early strength (3d compressive strength ≥15MPa) and excellent long-term mechanical properties and durability (28d compressive strength ≥52MPa, sulfate erosion resistance coefficient K≥1.1). It is particularly suitable for high-performance concrete engineering in harsh sulfate erosion environments such as marine engineering, salt lakes, and saline-alkali land, and has broad application prospects.
[0021] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Detailed Implementation
[0022] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, the following, in conjunction with the appendix and preferred embodiments, details the specific implementation methods and effects of a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, its preparation method, and its application, based on the present invention. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, the results of one or more embodiments can be combined in any suitable manner. These embodiments are provided to make the invention thorough and complete, and to fully express the scope of the invention to those skilled in the art. It should be noted that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values described in these embodiments should be interpreted as merely exemplary and not as limiting.
[0023] This invention proposes a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades and its preparation method. The technical solution uses decommissioned wind turbine blade powder as a partial silica-alumina raw material to prepare cement clinker with a specific mineral phase composition. This decommissioned wind turbine blade cement clinker is then scientifically compounded with granulated blast furnace slag powder, silica fume, gypsum, and fly ash, and then co-milled to obtain the sulfate-resistant silicate cement composite cementitious material. The specific steps are as follows: The first step is raw material pretreatment and storage: natural raw materials such as limestone, clay, bauxite, iron ore, and sandstone are crushed by crushing equipment and sent to a drying and grinding system (such as a vertical mill) to grind to ≤10% residue on an 80μm sieve. This increases the reaction surface area, promotes carbonate decomposition and solid-phase reaction, reduces calcination difficulty and energy consumption, and obtains qualified raw material powder which is then stored in its respective batching warehouse.
[0024] Decommissioned wind turbine blades are disassembled, and metal connectors are removed to eliminate impurities and ensure the purity of the clinker composition, thereby improving cement stability and safety. After coarse and fine crushing, the blades are ground in a specialized mill to a particle size of <80μm for over 90% of the particles. This significantly improves the reactivity of the blade powder and the uniformity of raw material mixing, allowing it to fully participate in clinker mineral formation and preventing agglomeration or unmelted particles from adversely affecting performance. The resulting decommissioned wind turbine blade powder is stored in a dedicated batching warehouse. Testing shows that its dry basis chemical composition meets the following conditions: SiO2 ≥ 50 wt%, Al2O3 ≥ 17 wt%, and loss on ignition ≤ 15 wt%.
[0025] In some specific embodiments of the present invention, it is preferred to use separate storage and dedicated ingredient preparation methods to avoid cross-contamination of raw materials, ensure accurate proportions and stable yield values, and improve the reliability of industrial production.
[0026] In some specific embodiments of the present invention, it is preferable to control the residue of the mixed raw material to ≤10% on an 80μm sieve, which further improves the calcinability of the raw material, makes the preheating decomposition more complete and the calcination more thorough, and ensures that the clinker minerals are well developed and have balanced and stable performance.
[0027] The raw materials used in this invention can be obtained from the market. To facilitate understanding of the raw material formulation design of this invention, the chemical composition of the raw materials used in the clinker firing process in subsequent specific embodiments was analyzed, and the results are shown in Table 1.
[0028] Table 1
[0029] Next comes the raw material batching and grinding. Specifically, the raw materials are batched according to the following proportions using a central control system (DCS) and quantitative feeding equipment: limestone 81.91–82.87%, clay 0.77–2.34%, bauxite 0.78–1.57%, iron ore 1.50–1.64%, sandstone 6.34–8.22%, and dried decommissioned wind turbine blade powder 5.0–7.0%. Each raw material powder (including decommissioned wind turbine blade powder) is precisely metered and transported to the raw material grinding system. A vertical mill or tube mill is used for closed-circuit grinding and drying of the mixture to ensure that the residue on the 80μm sieve of the discharged raw material powder is ≤10%, and that the chemical composition is uniform and stable.
[0030] The raw material ratio described in this invention is within an feasible range. Those skilled in the art can stably produce clinker that meets the mineral composition requirements by combining this ratio range with conventional raw material blending and calcination processes, without the need for creative labor.
[0031] The chemical composition analysis results in Table 1 show that the decommissioned wind turbine blade powder contains a relatively high amount of MgO (approximately 9.35%). However, in cement clinker, excessively high MgO content may form periclase, which can cause expansion stress during long-term slow hydration in concrete, thus threatening the later-stage volume stability. This invention, through strict control of raw material proportioning design, controls the content of decommissioned wind turbine blade powder to ≤7.0% (dry basis), comprehensively considering the balance between its effective substitution as a silica-alumina raw material and avoiding the introduction of excessive MgO, ensuring that the MgO content in the final clinker is within a safe limit. This utilizes solid waste while avoiding the potential risks posed by periclase, ensuring the long-term volume stability of the clinker.
[0032] Under this premise, this invention, through careful ingredient design, controls the raw meal ratios within the following ranges: lime saturation coefficient KH: 0.88–0.93; silica content SM: 2.6–2.8; alumina content IM: 1.5–1.7. Through theoretical calculations and experimental verification, under this ratio system, after subsequent raw meal preheating and pre-decomposition, clinker calcination, and rapid cooling steps, this invention can stably obtain cement clinker with a mineral composition of C3S 72.0–80.0%, C2S 6.0–14.8%, C3A ≤ 3.6%, and C4AF 9.9–10.7%, with a total C3S and C2S content ≥ 85%. Its C3S content is as high as 72% or more, ensuring excellent early strength in both the resulting cement clinker and the final composite cementitious material. Simultaneously, its C3A content does not exceed 3.6%, laying the foundation for the high sulfate resistance of the final cementitious material from a mineral composition perspective.
[0033] In the above technical solution, the raw material preheating and pre-decomposition, clinker calcination, and rapid cooling steps can be carried out using conventional raw material firing methods in this technical field, and the present invention does not impose specific limitations. The following process description is merely illustrative and is not intended to limit the technical solution of the present invention.
[0034] In some specific embodiments of the present invention, raw meal preheating and pre-decomposition involves feeding homogenized raw meal powder into a cyclone preheater system, where it is suspended and subjected to countercurrent heat exchange with high-temperature exhaust gas from a rotary kiln, being heated to 800-900°C. During this process, most of the carbonates are decomposed. Subsequently, the raw meal is fed into a decomposition furnace, where it undergoes further decomposition under the high-temperature environment generated by fuel combustion. Then, the decomposed material is fed back into the rotary kiln for sintering at approximately 1450°C. The material is held at the high-temperature section of the kiln for about 60 minutes to ensure the clinker's mineral phase composition meets the design specifications. Finally, the high-temperature clinker is discharged from the rotary kiln and immediately fed into a high-efficiency grate cooler, where it is rapidly cooled to below 100°C within minutes by a large volume of cooling air to stabilize the highly reactive mineral crystals, resulting in high-C3S, low-C3A content cement clinker for decommissioned wind turbine blades.
[0035] This invention enables retired wind turbine blade powder to effectively replace natural clay, sandstone and other mineral resources through the above-mentioned raw material preparation and clinker firing, realizing the high-value utilization of bulk solid waste, reducing resource consumption and carbon emissions in cement production, while optimizing the mineral composition of clinker, increasing C3S content, reducing C3A content, and improving cement durability.
[0036] After the cement clinker for retired wind turbine blades is prepared and cooled, it is transported to a clinker silo for storage and future use.
[0037] In some specific embodiments of the present invention, the mixture is ground with granulated blast furnace slag powder, silica fume, gypsum, and fly ash as required. The specific proportions are as follows: by mass percentage, 32-40% cement clinker from decommissioned wind turbine blades, 42-50% granulated blast furnace slag powder, 5-9% silica fume, 3-5% gypsum, and 5-8% fly ash; the raw materials are measured and mixed according to the above design proportions, and then the mixture is ground to a specific surface area ≥ 420 m². 2 / kg, to obtain a sulfate-resistant silicate cement composite cementitious material.
[0038] In the above technical solution, gypsum is used as a retarding component, and its dosage can be adjusted within the range of 3-5%. When the gypsum dosage is 3%, the basic retarding requirement can be met. When the dosage is 5%, the workability of the slurry can be further improved. 4% is the optimal balanced dosage, all of which can achieve normal setting and strength development of cementitious materials.
[0039] In the above technical solution, the content of granulated blast furnace slag powder is controlled at 42-50%. This range can ensure sufficient pozzolanic activity to consume calcium hydroxide and improve corrosion resistance, while avoiding insufficient early strength due to excessive content. Those skilled in the art can implement this within this range and obtain the expected performance.
[0040] In some specific embodiments of the present invention, the granulated blast furnace slag powder is preferably S95 grade or higher, which has a high activity index, fine particle size, and matched hydration rate, allowing it to fully react with clinker hydration products and reduce the calcium hydroxide content in the system. Slag powder below S95 grade has insufficient activity and cannot achieve the expected sulfate attack resistance effect; therefore, it is limited to S95 grade or higher. This ensures that the slag powder has high pozzolanic activity and low water demand, thereby enabling it to react more effectively with calcium hydroxide, a product of cement clinker hydration, optimizing the microstructure of the slurry, and further improving the long-term strength and sulfate attack resistance of the composite cementitious material.
[0041] In the above technical solution, by using high-C3S clinker as the strength foundation and introducing an ultra-high proportion of granulated blast furnace slag powder and active admixtures such as silica fume, a pozzolanic reaction occurs in the slurry, effectively consuming the large amount of calcium hydroxide generated during clinker hydration. This fundamentally eliminates the main intrinsic conditions for sulfate attack to generate expansive products. The resulting cementitious material thus possesses both high early-age strength and ultimate resistance to sulfate attack, with measured 3-day compressive strength ≥15MPa, 28-day compressive strength ≥52MPa, and 28-day corrosion resistance coefficient K ≥1.1.
[0042] The present invention also proposes the application of the sulfate-resistant silicate cement composite cementitious material prepared according to the aforementioned method in the field of concrete or building materials technology.
[0043] The present invention will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention still fall within the scope of protection of the present invention.
[0044] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0045] Examples 1-9 This embodiment prepares a cement clinker for decommissioned wind turbine blades and uses this cement clinker to formulate a sulfate-resistant silicate cement composite cementitious material. The chemical composition of the raw materials used to prepare the cement clinker for decommissioned wind turbine blades is shown in Table 1. The specific steps are as follows: (1) Raw material pretreatment and storage: Natural raw materials such as limestone, clay, bauxite, iron ore, and sandstone are crushed separately by crushing equipment and then fed into a drying and grinding system (such as a vertical mill) to grind until the residue on an 80μm sieve is ≤10%, obtaining qualified raw material powder and storing it in its respective batching warehouse. The retired wind turbine blades are disassembled, the metal connectors are removed, and after coarse and fine crushing, they are ground by a special mill to a particle size of more than 90% < 80μm to obtain retired wind turbine blade powder, which is then stored in a special batching warehouse. (2) Raw material batching and raw material grinding: The raw materials are batched by mass according to the following proportions: limestone 82.29%, clay 2.04%, bauxite 0.78%, iron ore 1.55%, sandstone 6.34%, and dried wind turbine blade powder 7.00%. The powders of each raw material (including powder from decommissioned wind turbine blades) are quantitatively transported to the raw material milling system. The mixture is then ground and dried in a closed-circuit mill using a vertical mill or tube mill to ensure that the residue on the 80μm sieve of the raw material powder is ≤10% and that the chemical composition is uniform and stable. (3) Raw material preheating and predecomposition: The homogenized raw meal powder is fed into a cyclone preheater system, where it exchanges heat countercurrently with the high-temperature exhaust gas from the rotary kiln in a suspended state, and is heated to 800~900℃ to complete the decomposition of most of the carbonates; then it enters the decomposition furnace, where the raw meal is fully decomposed in the high-temperature environment generated by fuel combustion. (4) Calcination of clinker: The decomposed material enters the rotary kiln and undergoes a sintering reaction at a temperature of 1450℃. The material is held at this temperature for 60 minutes to ensure that the mineral phase composition of the clinker meets the design requirements. (5) Rapid cooling of clinker: After the high-temperature clinker is discharged from the rotary kiln, it immediately enters the high-efficiency grate cooler, where it is rapidly cooled to below 100°C by a large amount of cooling air within minutes. (6) Clinker storage and grinding: After the clinker cools, it is mixed by weight according to the following proportions: 32% clinker, 50% slag powder (S95), 9% silica fume, 4% gypsum, and 5% fly ash (Grade I). The mixture is then fed into a cement grinding system (such as a ball mill or vertical mill) and ground until the specific surface area is 435 m² / kg. This yields a sulfate-resistant silicate cement composite cementitious material.
[0046] Examples 1-9 were all prepared according to the above method, the difference being the different raw material ratios, the specific conditions of which are shown in Table 2. The test results of the gelling materials prepared by the examples are shown in Table 2.
[0047] Table 2
[0048] As shown in Table 2, the 3-day flexural strength of the cementitious materials in each embodiment is 3.5~4.6 MPa, the 3-day compressive strength is 15.5~23 MPa, the 28-day flexural strength is 7.8~8.2 MPa, the 28-day compressive strength is 54~58 MPa, and the 28-day corrosion resistance coefficient K is 1.15~1.18, that is, the 28-day compressive strength is ≥52 MPa and the 28-day corrosion resistance coefficient K is ≥1.1. The performance indicators meet the expectations of this invention.
[0049] The technical features in the claims and / or specification of this invention can be combined, and the combination is not limited to the combinations obtained through reference in the claims. Technical solutions obtained by combining the technical features in the claims and / or specification are also within the scope of protection of this invention.
[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, characterized in that, The raw materials, by mass percentage, include: 32-40% cement clinker from decommissioned wind turbine blades, 42-50% granulated blast furnace slag powder, 5-9% silica fume, 3-5% gypsum, and 5-8% fly ash; wherein, by mass percentage, the mineral composition of the cement clinker from decommissioned wind turbine blades includes: C3S 72.0-80.0%, C2S 6.0-14.8%, C3A≤3.6%, C4AF 9.9-10.7%, and the total amount of C3S and C2S ≥85%.
2. The sulfate-resistant silicate cement composite cementitious material according to claim 1, characterized in that, Its specific surface area is ≥420 m² 2 / kg.
3. The sulfate-resistant silicate cement composite cementitious material according to claim 1, characterized in that, Its 3d compressive strength is ≥15MPa, 28d compressive strength is ≥52MPa, and 28d corrosion resistance coefficient K is ≥1.
1.
4. A method for preparing a sulfate-resistant silicate cement composite cementitious material based on cement clinker from decommissioned wind turbine blades, characterized in that, It includes the following steps: measuring and mixing raw materials according to the designed proportions, and grinding the mixture to a specific surface area ≥ 420 m². 2 / kg, to obtain cementitious material; by mass percentage, the raw materials include: 32~40% cement clinker from decommissioned wind turbine blades, 42~50% granulated blast furnace slag powder, 5~9% silica fume, 3~5% gypsum, and 5~8% fly ash; by mass percentage, the mineral composition of the cement clinker from decommissioned wind turbine blades includes: C3S 72.0~80.0%, C2S 6.0~14.8%, C3A≤3.6%, C4AF 9.9~10.7%, and the total amount of C3S and C2S ≥85%.
5. The preparation method according to claim 4, characterized in that, The cement clinker for the decommissioned wind turbine blades is prepared according to the following steps: raw materials are measured and mixed according to the designed proportions; the mixture is ground to obtain raw meal; the raw meal is preheated, decomposed, calcined, and cooled to obtain clinker containing decommissioned wind turbine blades; The raw materials for preparing the raw meal, by weight percentage, include: limestone 81.91-82.87%, clay 0.77-2.34%, bauxite 0.78-1.57%, iron ore 1.50-1.64%, sandstone 6.34-8.22%, and degraded wind turbine blade powder (dried basis) 5.0-7.0%.
6. The preparation method according to claim 5, characterized in that, The decommissioned wind turbine blade powder is obtained by dismantling decommissioned wind turbine blades, removing metal connectors, coarse crushing, fine crushing and grinding, wherein more than 90% of the particles have a particle size of <80μm.
7. The preparation method according to claim 6, characterized in that, By mass percentage, the decommissioned wind turbine blade powder contains ≥50% SiO2, ≥17% Al2O3, and ≤15% loss on ignition.
8. The preparation method according to claim 5, characterized in that, The residue of the raw material on an 80μm sieve is ≤10%.
9. The preparation method according to claim 4, characterized in that, The granulated blast furnace slag powder is of grade S95 or higher.
10. The application of a sulfate-resistant silicate cement composite cementitious material according to any one of claims 1 to 3 or a sulfate-resistant silicate cement composite cementitious material prepared by the preparation method according to any one of claims 4 to 9 in the field of concrete or building materials technology.